Ion Chromatographic Analysis of Major Electrolyte Cations in Sappan Wood Extract (Caesalpinia sappan L.) - Amin, Muhammad; Sedyohutomo, Anang; Amin, Nahdiah; Ibrahim, Abu Rahmat; Mauraji, Ilham (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
Using ion chromatography, a convenient method for analyzing major electrolyte cations (lithium, sodium, ammonium, potassium, magnesium, calcium, strontium, and barium) was presented and applied to Sappan wood samples. The analysis used a Metrohm C4-150/4.0 column with nitric acid (HNO3) as the eluent. Optimal separation was achieved with an eluent flow rate of 0.8 mL/min, resulting in excellent peak resolution and complete separation within 20 min. Calibration curves for all targeted cations were established within the 0.5 to 20.0 mg/L concentration range, demonstrating strong linearity with correlation coefficients (R2) greater than 0.999, ensuring accurate and reliable analysis. The Sappan wood samples were obtained from Ternate City, North Maluku, where cation concentrations were varied based on the extraction method. Boiling the sappan wood samples, as compared to soaking in hot purified water, significantly increased the release of electrolyte cations, resulting in higher concentrations and a greater variety of cations. Calcium was the most abundant cations in each extraction method, with a concentration of 37.80 mg/kg (5 min soaking), 43.92 mg/kg (10 min soaking), and 83.73 mg/kg (10 min boiling). In contrast, the concentration of three electrolyte cations: lithium, strontium, and barium, was below the instrument’s detection limit in all the samples.